TEAMS GAMES TOURNAMENT SEBAGAI UPAYA PENINGKATAN KEMAMPUAN BELAJAR MAHASISWA PADA MATA KULIAH MATEMATIKA EKONOMI - FACHRURROZIE, -; Anisyukurillah, Indah (Fakultas Ekonomi, Universitas Negeri Semarang, 2009)
The objective of this study is to measure and obtain the empirical proof that concerned to theÃ‚Â effectiveness and significance in applying Teams Games Tournament learning model that was presented in teaching learning process in Economics Mathematics subject in improving theÃ‚Â studentsÃ¢â‚¬â„¢ learning ability. This study used 3 cycles and involved 67Ã‚Â studentsÃ‚Â from the 1st semesterÃ‚Â of regular class, Accounting Education Program, S1 Degree on Accounting Department, Economics Faculty, Semarang State University. Result of this study was to apply Economics Mathematics through Teams Games Tournament model learning in Quadrat Function Topic with the sub topics were Demand Function, Supply Function, Market Equilibrium, Tax and Subsidy Influences to improve the studentsÃ¢â‚¬â„¢ ability and skill in teaching learning process.Ã‚Â It was seen that score average from 11 teams from Cycle I, II and III was getting increased about 60,11%; 87% and 96,88%. Therefore, that result has obtained the target because the studentsÃ‚Â who got the score higherÃ‚Â than 70 wereÃ‚Â more than 80 %, thus this teaching method can be said successfull. Key Words : Teams Games Tournament,Economics Mathematics